Clinical significance of extraskeletal computed tomography findings on 18F-NaF PET/CT performed for osseous metastatic disease evaluation. Issue 9 (September 2016) - Guo, H. Henry; Moradi, Farshad; Iagaru, Andrei
Abstract : Purpose: Extraskeletal findings detected on whole-body low-dose unenhanced computed tomography (CT) as a part of 18 F-NaF PET/CT scans can be numerous and present challenges for further management. Here, we investigate the frequency and clinical significance of extraskeletal findings among 130 consecutive patients undergoing 18 F-NaF PET/CT for osseous metastatic disease. Methods: 18 F-NaF PET/CT performed on 130 patients (101 men and 29 women; mean age: 61.4 years) with biopsy-proven malignancies were reviewed independently. Incidental soft tissue findings detected on unenhanced low-dose CT portions of the scans were compiled and categorized by clinical significance. Results: A total of 275 incidental extraskeletal CT findings were observed in 114 out of 130 patients (87.7%). Seven patients (5.4%) showed clinically significant findings. One patient developed new lung nodules that were resected and proven to be metastases. Two patients showed new hypodense hepatic lesions that were highly suspicious for liver metastases. One patient with prostate cancer was found to have previously unknown retroperitoneal lymphadenopathy. Three patients showed indeterminate renal and adrenal lesions that necessitated further correlative imaging. Conclusion: Although CT indicated a large number of incidental extraskeletal lesions in the majority of patients undergoing 18 F-NaF PET/CT, clinically significant incidental findings requiring further evaluation were relatively infrequently observed in 5.4% of patients. Thus, the low-dose unenhanced CT in 18 F-NaF PET/CT performed for oncologic evaluation may indicate unexpected soft tissue lesions that can impact patient management and therefore should be interpreted by physicians skilled in CT reading, with correlation to available imaging, and familiar with established guidelines for work-up of incidental findings.